ChemInform Abstract: Speradines B—D, Oxygenated Cyclopiazonic Acid Alkaloids from the Sponge‐Derived Fungus Aspergillus flavus MXH‐X104. Issue 38 (3rd September 2015) - Ma, Xinhua; Peng, Jixing; Wu, Guangwei; Zhu, Tianjiao; Li, Guoqiang; Gu, Qianqun; Li, Dehai
Abstract isolation, structure elucidation and bioassay screening